Strategi Manajerial dan Capaian Mutu Sekolah - Suandi; Syarif. A. Syukur; Usman Radiana; Tulus Junanto (Medan Resource Center, 2022)
This study seeks to examine the impact of the implementation of manage- rial strategies undertaken by principals on the achievement of principals' quality. Managerial strategies in this study are measured into three strat- egies: 1) the effectiveness of school management, 2) strengthening the competence of graduates, 3) empowering teachers and staff. This re- search using quantitative research and sample in this study SMK Negeri 1 Semparuk through panel data regression analysis. The results showed that managerial strategy signif- icantly influenced the achievement of school quality. The effectiveness of school management strategies has a significantly positive effect on school quality outcomes, strategy of strengthening the competencies of gradu- ates and empowering teachers and staff has no significant effect on the achievement of school quality. As a recom- mendation, school principals should encourage graduate competencies through empowering teachers and staff to be actively involved so that school quality can be achieved.